The Effect of Employee Engagement and Work Motivation on Performance with Learning Agility as an Intervening Variable at PT. Paiton Operation and Maintenance Indonesia - Achmad Taufik; Sri Wahyu Lelly Hana Setyanti; Markus Apriyono; Rochman Hidayat (Budapest International Research and Critics University, 2022)
This study aims to examine and analyze the direct and indirect effects of employee engagement and work motivation on performance through learning agility on the performance of employees of PT. Paiton Operation and Maintenance Indonesia (PT. POMI). This research was conducted on employees of PT. POMI with the number of respondents in this study as many as 124 people. The sampling technique used is simple random sampling where the sample is taken at random from the entire population. Data analysis method using Partial least square using softwareSMART PLS 3. HasThe results showed that work motivation and learning agility directly had a positive and significant effect on performance, while employee engagement directly had a positive but not significant effect on performance. The work motivation and employee engagement indirectly have a positive and significant effect on performance.